Organic Acid Salt from Complete Feed Silage Corn Based by Product as an Alternative to Substitute Antibiotic Function as a Growth Promotor for Broiler - Negara, W; Ridla, M; Lubis, AD; Winarsih, W; Surachman, M; Darmawan, IWA; Santoso, Santoso (ANIMAL PRODUCTION, 2009)
This study was designed to evaluate the efficacy of organic acid salt Zn from complete feed silage based on corn by product as an alternative to subtitute antibiotic function as a growth promotor for broiler. Ninety day old commercial Cobb broiler chickens were randomly distributed into six groups having three replicates of five birds in each group. Negative control (R0) birds were offered standard basal diet and no challenged, positive control (R1) birds were offered standard basal diet and challenged with 107 Salmonella typhimurium. Treatment R2, R3, R4 and R5 were challenged by 107 CFU of Salmonella typhimurium which added in feed with 0.1% flouroquinolone, 0.1%, 0.2%, and 0.3% of organic acid salts. The result showed that dietary of organic acid salts affect consumption, weight gain, and final body weight (P<0.05). Meanwhile, feed conversion (FCR) was not affected by antibiotics norÂ  organic acids. Our conclusion, Dietary organic acid salt from complete feed silage corn based by product until dose 0.2% can improve the performance of broiler chickens infected Salmonella typhimurium. (Animal Production 11(3): 170-175 (2009)Â Key Words: broiler, organic acid, Salmonella typhimurium